ANALISIS STRATEGI PEMASARAN PRODUK PEMBIAYAAN MURABAHAH DALAM UPAYA MENINGKATKAN JUMLAH NASABAH KSPPS BAYTUL IKHTIAR CABANG PAMIJAHAN BOGOR - Nuralfiah, Siti; Thantawi, Tubagus Rifqy; Nurhasan, Abdul Khodir (SAHID BANKING JOURNAL, 2024)
The development of the era of the economic system is growing. Indonesia now has many financial institutions with sharia principles, one of which is KSPPS Baytul Ikhtiar, a community economic institution that seeks to develop productive and investment businesses in order to increase its business activities based on sharia principles.The research method uses descriptive qualitative analysis with a type of field research. The research subject is KSSPS Baytul Ikhtiar. The data collection technique used is the method of observation, interviews and documentation. Data analysis techniques with data collection, data reduction, data presentation and drawing conclusionsThe research method uses descriptive qualitative analysis with the type of field research. Data collection was carried out using the methods of observation, interviews and documentation. Data analysis techniques with data collection, data reduction, data presentation and drawing conclusions.The results of this study are first The marketing strategy implemented at KSPPS Baytul Ikhtiar Pamijahan Branch can attract people's interest in becoming members so that the number of members every month always increases. The promotion strategies used by KSPPS Baytul Ikhtiar include direct sales promotion, publicity and word of mouth. Second, The obstacles encountered in marketing KSPPS Baytul Ikhtiar financing products are competition for bank & other financial institution products, lack of public knowledge, resistance, and internal field staff who lack knowledge and understanding of institutional products. Settlements made in an effort to increase customers by collaborating with baytulmall by holding social activities in an area.